Disruptive innovation in media industry ecosystem and need for improving managerial cognitive capabilities in polymediation era - Masoud Gholampour Rad (Cogent Business & Management, 2017)
Media industry ecosystem has undergone major transformations due to emergence of disruptive innovations. When industry ecosystem incumbents have dynamic organizational capability and make necessary strategic changes, they could exploit disruptive innovations. Managers' cognitive capabilities, dynamic organizational capabilities, and strategic changes are three variables that have key relationships; therefore, this research focuses on this relation. Since dominant logic reflects the internal relation of managers' cognitive capabilities, dynamic organizational capabilities and strategic changes, in this research the relationship between two variables of disruptive innovation (DI) and dominant logic (DI) has been evaluated. IRIB organization top managers replied to questionnaire. Both types of causal and correlation relations of two variables were evaluated by PLS technique. Research findings reveal 3 indexes and 10 attributes related to DI variable and three indicators and eight attributes related to DI. This model has good fitness and reveals the necessity of improving managers' recognition of digitalization phenomenon as disruptive innovation and undertaking new dominant logic and related strategic actions. Organizations lack the power of exploiting disruptive innovation if they don't improve managers' recognition of digitalization phenomenon, not create dynamic organizational capabilities and not welcome strategic changes.
Keywords: 650